2012
DOI: 10.1111/j.1365-2966.2012.21945.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of multiphase cold accretion in a massive galaxy at z = 0.7

Abstract: We present detailed photo+collisional ionization models and kinematic models of the multiphase absorbing gas, detected within the Hubble Space Telescope(HST)/COS, HST/STIS and Keck/HIRES spectra of the background quasar TON 153 at 104 kpc along the projected minor axis of a star-forming spiral galaxy (z = 0.6610). Complementary g r i Ks photometry and stellar population models indicate that the host galaxy is dominated by an ∼4 Gyr stellar population with slightly greater than solar metallicity and has an esti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 97 publications
(254 reference statements)
1
43
0
Order By: Relevance
“…For example, kinematic studies of some Lyα nebulae suggest rotational velocities and inflow rates consistent with those expected for these inspiraling streams (Martin et al 2014;Prescott et al 2015). Similarly, absorption line studies are beginning to emphasize the bimodal distribution of absorption detections, where detections along the galaxy's minor axis tend to show absorption properties consistent with outflowing gas, while detections roughly along the galaxy's major axis demonstrate properties (such as corotational inflow) that are consistent with inspiraling cold streams (Kacprzak et al 2010(Kacprzak et al , 2012a(Kacprzak et al , 2012bBouché et al 2012Bouché et al , 2013Crighton et al 2013;Nielsen et al 2015;Bouché et al 2016;Ho et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, kinematic studies of some Lyα nebulae suggest rotational velocities and inflow rates consistent with those expected for these inspiraling streams (Martin et al 2014;Prescott et al 2015). Similarly, absorption line studies are beginning to emphasize the bimodal distribution of absorption detections, where detections along the galaxy's minor axis tend to show absorption properties consistent with outflowing gas, while detections roughly along the galaxy's major axis demonstrate properties (such as corotational inflow) that are consistent with inspiraling cold streams (Kacprzak et al 2010(Kacprzak et al , 2012a(Kacprzak et al , 2012bBouché et al 2012Bouché et al , 2013Crighton et al 2013;Nielsen et al 2015;Bouché et al 2016;Ho et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There is even indication that local extended H I disks may be environmentally dependent on the galaxy's filamentary environment (Courtois et al 2015). At moderate redshift (z∼0.5-1.5), numerous absorption line studies of the circumgalactic medium of galaxies have begun to emphasize the bimodal properties of absorbers, where absorption along the galaxy's major axis tends to show high angular momentum (co-rotating) inflow, and absorption along the galaxy's minor axis shows observational signatures of outflow (Kacprzak et al 2010(Kacprzak et al , 2012a(Kacprzak et al , 2012bBouché et al 2012Bouché et al , 2013Crighton et al 2013;Nielsen et al 2015;Bouché et al 2016;Diamond-Stanic et al 2016;Ho et al 2017). At higher redshift (z∼2-3), kinematic studies of Lyα "blobs" have observed large-scale rotation consistent with high angular momentum cold gas accretion (Martin et al 2014;Prescott et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…All the properties so far derived for the pLLSs and LLSs fit with the gas properties found in the simulated cold flow accretion: the N HI range, the low metallicities, the temperatures, densities, length scales, and even some of the galaxy properties (e.g., Ribaudo et al 2011b;Kacprzak et al 2012b;Lehner et al 2013). However, it is unknown from these observations if the gas is actually accreting onto the galaxies.…”
Section: Gas Accretion Via Pllss and Llss?mentioning
confidence: 83%
“…Several Mg II surveys have demonstrated that a class of strong Mg II absorbers at small impact parameters (ρ 40 kpc) are primarily found along the galaxies' minor axes, consistent with an origin from large-scale outflows (e.g., Bordoloi et al 2011;Kacprzak et al 2012a;Bouché et al 2012). However, Kacprzak et al (2012b) has also shown one example of a very metal-poor LLS observed projected along the minor axis of the associated galaxy albeit at a projected distance of 104 kpc. Evidently all absorption detected in the spectra of QSOs probing gas along the projected minor axis of galaxies may not be produced by winds, especially at these large impact parameters.…”
Section: Gas Accretion Via Pllss and Llss?mentioning
confidence: 99%
“…The paradigm developed thus far is that the Mg ii absorbers are linked with either of the galactic-scale outflows originating from their host galaxies (Bouché et al 2006;Tremonti et al 2007;Weiner et al 2009;Martin & Bouché 2009;Noterdaeme et al 2010;Chelouche & Bowen 2010; ⋆ E-mail: rjoshi@iucaa.in(RJ) Rubin et al 2010;Lundgren et al 2012;Bordoloi et al 2014), dynamical mergers or filamentary accretion on to galaxies (Steidel et al 2002;Chen et al 2010a;Kacprzak et al 2010Kacprzak et al , 2011Kacprzak et al , 2012Martin et al 2012;Rubin et al 2012) and high velocity clouds [HVCs] (Richter 2012;Herenz et al 2013). Thus Mg ii absorbers may be tracing different feedback processes that control the evolution of their host galaxies.…”
Section: Introductionmentioning
confidence: 99%